Situating Transnational Genre Knowledge: A Genre Trajectory Analysis of One Student's Personal and Academic Writing. (July 2014) - Rounsaville, Angela
Scholars have recently begun to conceive of literacy practices as drawing from resources that are simultaneously situated and extracontextual. In particular, studies of transnational literacy affirm the importance of both locality and movement in literacy studies. Continuing this inquiry into the situated and dispersed nature of transnational literacy, the author investigates the distinct effects that shuttling between national contexts have on the accumulation and use of genre knowledge. Specifically, through a case study of one Third Culture Kid student writer, the author reports on how her genre knowledge develops in response to transnational relocations between Italy and the United States and the way this transnational genre knowledge informs her writing of a high-stakes in-school genre. This case illustrates the value of rhetorical genre studies for understanding the situated and dispersed nature of transnational literacy and begins to outline the distinctiveness of transnational boundary-crossing practices.